2004
DOI: 10.1016/j.jvs.2004.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Serum values of metalloproteinase-2 and metalloproteinase-9 as related to unstable plaque and inflammatory cells in patients with greater than 70% carotid artery stenosis

Abstract: Elevated MMP-9 concentration is associated with carotid plaque instability and the presence of macrophages, factors that indicate increased risk for a neurological event. Determination of this gelatinase may enable identification of high-risk subgroups of patients with carotid artery stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
1
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 19 publications
(24 reference statements)
4
58
1
8
Order By: Relevance
“…98,99 Macrophage activity quantified by PET 100 and neovascular angiogenesis assessed by MRI have been observed in experimental models. 101 Biomarkers such as C-reactive protein and certain matrix metalloproteinases with the potential to identify carotid plaque instability have also been investigated, [102][103][104] but the reliability of biomarkers in predicting clinical events has not been established. Several studies have shown that plaque composition is modified by treatment with statins.…”
Section: Characterization Of Atherosclerotic Lesions In the Extracranmentioning
confidence: 99%
“…98,99 Macrophage activity quantified by PET 100 and neovascular angiogenesis assessed by MRI have been observed in experimental models. 101 Biomarkers such as C-reactive protein and certain matrix metalloproteinases with the potential to identify carotid plaque instability have also been investigated, [102][103][104] but the reliability of biomarkers in predicting clinical events has not been established. Several studies have shown that plaque composition is modified by treatment with statins.…”
Section: Characterization Of Atherosclerotic Lesions In the Extracranmentioning
confidence: 99%
“…A significant increase in MMP-9 immunopositivity has also been demonstrated in atherosclerotic lesions of the aorta and carotid artery of rabbits fed a high-cholesterol diet [161]. Increased plasma levels of circulating MMP-9, as well as MMP-2, also correlate with the clinical symptoms of plaque instability and rupture in the coronary and cerebral circulation [162,163] as well as being found in patients affected by myocardial infarction [164,165], suggesting that MMP-9 may be useful as a biomarker for acute coronary syndrome [166,167].…”
Section: Introductionmentioning
confidence: 96%
“…1 Elevated serum MMP-9 concentration is associated with carotid plaque instability and the presence of infiltrated macrophages. 2 Furthermore, analysis of the presence of MMP-9 protein by ELISA within excised carotid plaques revealed high MMP-9 protein mass in calcified segments at or near the carotid bifurcation and in segments with intraplaque hemorrhage. Gelatin zymography showed an increased gelatinase activity of MMP-9 in these segments.…”
mentioning
confidence: 99%